Understanding trends in biological invasions by introduced mammals in southern South America: a review of research and management - Ballari, Sebastián A. (2016)
Invasive introduced mammals (IIMs) have ecological and social dimensions that require holistic research to integrate academic disciplines with basic and applied sciences. We assessed current knowledge of IIMs to determine trends in their study and management in southern South America. A keyword search was used to select indexed papers in the Web of Science. These were reviewed to assess each study's objective, methodology, country, publication year, and taxa. Unpublished ‘grey’ literature was added to evaluate further each species’ native range, year of introduction, the reason for its introduction, its distribution, dispersal pathways, impacts, and management. Most of the 190 peer‐reviewed publications were focused on autecology and impacts of IIMs; less than 4% addressed management or social topics. Twenty‐three IIMs have been documented in the study area. The southern Magellanic subpolar forest was the most invaded ecoregion (17 spp.), and the most studied orders, from 440 records in 190 papers, were Artiodactyla (35%) and Rodentia (28%). Together, livestock and commensals brought during early European colonisation constituted 44% of this assemblage, but hunting was the major reason behind the introduction of IIMs (30%). To enhance policies and institutional frameworks pertaining to biological invasions, we highlight the importance of: 1) recognising the presence and spread of IIMs in ‘pristine’ or protected areas; 2) improving controls to prevent new introductions and escapes; 3) including social and cultural aspects of biological invasions in research and management plans; 4) reinforcing hunting regulations; 5) establishing long‐term programmes to monitor distribution and dispersion; 6) creating mechanisms for scientists and managers to co‐produce research and policy programmes oriented towards applied issues; 7) developing pilot management projects in critical areas; 8) achieving societal involvement in management programmes to ensure public acceptance; and 9) developing prioritisation tools, as resources needed to manage IIMs are often limited.